Transdisciplinary Approaches on Reconciliation Research: Studies in Honor of Martin Leiner - Ferrari, Francesco; Tacchini, Davide; Villanueva, Laura; Gurstein, Binyamin; Barakat, Zeina; Basuchoudhary, Atin; Freytag, Andreas; Bourgine, Benoît; O'Malley, Martin; Peña, Luis (Research in Peace and Reconciliation, 2024)
Reconciliation studies are concerned with the processes of rebuilding and improving damaged relationships after major wrongdoings. They focus on factors such as law, economics, and international relations, as well as on elements such as emotions and ethics, culture and religion, media and education. Reconciliation research therefore requires a transdisciplinary approach, to analyse both the procedures leading to the recognition of truth as well as those in which justice is administered; both the impact of public apologies and cooperation agreements; both the implementation of memory policies and civil society initiatives; both the outcomes of trauma therapy and intergenerational encounter groups. While on the surface the relationships in question are those between states, groups, organisations, and individuals, at a deeper level reconciliation always addresses and involves many axes of damaged relationships: those with others (intergroup); those with one’s own group (intragroup); those with oneself; those with the environment; and those with transcendence. Reconciliation studies deal, therefore, with a much broader spectrum of relationships than that taken into consideration by neighbouring disciplines such as conflict resolution and peace studies. In this volume, Francesco Ferrari and Davide Tacchini brought together examples of Leiner’s approach to reconciliation studies as a cooperative project of different disciplines. The articles are divided into two sections: 1. A series of case studies about Japan-South Korea relations, German-Czech reconciliation, Nagorno-Karabakh conflict using the methods of Martin Leiner, Sayyid Qutb view of American society, and South Africans revisiting TRC. 2. A series of theoretical clarifications on reconciliation and moderation from a Palestinian point of view, evolutionary game theory looking at reconciliation processes by a team of economists, grace and reconciliation from a Catholic theological point of view, philosophical reflections on the concept of reconciliation after Auschwitz, cognitive and affective aspects in reconciliation from a Catholic theological point of view, ecology and spatiality of reconciliation seen by a social geographer, and political dimensions of reconciliation.